ESTUDIO DE LAS ENFERMEDADES DE TRANSMISIÓN SEXUAL Y SU IMPACTO EN LA SEXUALIDAD DE LOS ESTUDIANTES DE TERCER Y CUARTO AÑO DE BIOLOGÍA QUÍMICA Y LABORATORIO DE LA ESCUELA DE CIENCIAS DE LA FACULTAD DE CIENCIAS DE LA EDUCACIÓN HUMANAS Y TECNOLÓGIAS, PERIODO ACADÉMICO 2012- 2013. - Logroño León, Valeria Carolina (2014)
The present research work was centered in sexual transmission illness with the finality to identify the impact in thied and fourth year of Chemical Biology and Laboratory students of Faculty of Educational Sciences, Humanities and Technologies, it developed during 2012-2013 period, for this propose the objective to demonstrate the manner in which the study of sexual transmission illness influence in the students sexuality of third and fourth year, it was important to made emphasis in the reference´s frame eith the finality to make the problem approach, justification and importance. To continue realize a wide focusing the independent variable that correspond the study of sexual transmission illness (ITS) and dependent variable which is the impact of students sexuality, for this used a specialized bibliography, in seeks to provide relevance and scientific content in attempt to be a good contribution to society in general in quality to consultation and practical guidance to prevent this kind of illness. In research process used specific methods to research, supporting in types and designs, like population to correspond teachers and students applied the quality technique survery supporting the questios nnaire instrument, where obtained important data of each question and processed in statistics squares and graphics and can to realize the XVII analysis, interpretation and hypothesis testing and define conclusions and recommendations. The results achieved are frank and honest confidence by teachers and parents, prevention guidelines in sexual transmission illness topics, symptoms identification, contraceptive methods application and commitment to make guidelines of community link.